The Analysis of Maxims Found in The Novel of “Breath” - Suardana, I Putu Eka; Astiari, Komang (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
Maxims are Cooperative Principles proposed by Grice. As a form of conversation, the novel also uses the concept of Maxims. This study aims to analyze compliance with Grice's Cooperative Principles, especially the four maxims, namely Quality, Quantity, Relationship, and Manner, used in the utterances in the Breath novel. The method used in this study is qualitative research. The subjects of this study are the conversations in the novel that contain four maxims, namely the Maxims of Quality, Quantity, Relationship, and Manner. The data collection method uses documentation techniques, namely reviewing and recording dialogues in the novel that are relevant to Grice's maxims. Meanwhile, the data analysis method uses grounded theory steps, including selecting, breaking down, and grouping conversations based on the types of maxims used. This results in findings that represent the complexity and dual function of communication. The research findings show that there are 2 Maxims of Quality, 5 Maxims of Quantity, 2 Maxims of Relationship, and 5 Maxims of Manner. The dominance of the Maxims of Quantity and Manner is very significant in this study. These maxims are used not only to make communication in Breath communicative but also to reveal that in one conversation, there is more than one Maxim used to show that communication in real life is complex and multifunctional.